Towards a New Competition Law: Some Comments on the Reform. Interview with Dr. Alejandro Falla Jara - Pinto Barrios, Jean Paul (2015)
The present interview seeks to give some points of view about the reform of Competency regulation. In that line, the interviewee give us his general opinion about the reform, the main contribution to the matter and those aspects that were missed, focusing his opinion on anti-competitive practice and negative regulation of anticompetitive practices.